Extracellular expression of agarolytic enzymes in Clostridium sp. strain and its application for butanol production from Gelidium amansii. (November 2022) - Xie, Wei; Zhang, Zhiqian; Bai, Shengkai; Wu, Yi-Rui
Graphical abstract: Highlights: Agarolytic genes of Aga0283 and NH2780 were over-expressed in strain WK-AN1. Butanol production was improved from agar in the presence of glucose. An optimal butanol production of 6.42 g/L was achieved from 17.86 g/L agar. Conversion of G. amansii was established to achieve a maximum of 7.83 g/L butanol. Abstract: In this study, Clostridium sp. strain WK-AN1 carrying both genes of agarase ( Aga0283 ) and neoagarobiose hydrolase ( NH2780 ) were successfully constructed to convert agar polysaccharide directly into butanol, contributing to overcome the lack of algal hydrolases in solventogenic clostridia. Through the optimization by the Plackett-Burman design (PBD) and response surface methodology (RSM), a maximal butanol production of 6.42 g/L was achieved from 17.86 g/L agar. Further application of utilizing the butyric acid pretreated Gelidium amansii hydrolysate demonstrated the modified strain obtained the butanol production of 7.83 g/L by 1.63-fold improvement over the wild-type one . This work for the first time establishes a novel route to utilize red algal polysaccharides for butanol fermentation by constructing a solventogenic clostridia-specific secretory expression system for heterologous agarases, which will provide insights for future development of the sustainable third-generation biomass energy.